Mapping of the mucolipidosis type IV gene to chromosome 19p and definition of founder haplotypes. - Slaugenhaupt, S A (1999)
Mucolipidosis type IV (MLIV) is a lysosomal storage disorder characterized by severe neurologic and ophthalmologic abnormalities. It is a rare autosomal recessive disease, and the majority of patients diagnosed, to date, are of Ashkenazi Jewish descent. We have mapped the MLIV gene to chromosome 19p13.2-13.3 by linkage analysis with 15 markers in 13 families. A maximum LOD score of 5.51 with no recombinants was observed with marker D19S873. Several markers in the linked interval also displayed significant linkage disequilibrium with the disorder. We constructed haplotypes in 26 Ashkenazi Jewish families and demonstrate the existence of two founder chromosomes in this population. The localization of MLIV to chromosome 19 will permit genetic prenatal diagnosis in affected families and will aid in the isolation of the disease gene.